Systematic Literature Review (SLR) Perkembangan Populasi Dan Ekonomi Islam Di Rusia - Credo Prasetyoadi Pangestu (Al Rikaz: Jurnal Ekonomi Syariah, 2024)
As the Muslim population in Russia increases, Muslim activists strive to seek innovations to develop the Islamic economy. Given the long history of Islam in this country, the challenges faced in advancing the Islamic economy are diverse. One of the most prominent challenges is the lack of certainty from the federal government in issuing official regulations for Islamic financial institutions. The presence of Islamophobia is suspected to be a factor in the revocation of the license of the first Islamic bank (Badr Forte Bank) due to allegations of violating laws on the Prevention of Money Laundering and Terrorism Financing. Therefore, mediators such as local Muftis and scholars are needed in this regard to socialize Sharia-compliant services to the public and convince the government to enhance the reputation of Sharia-compliant services in this country. They also have a crucial role in disseminating correct Islamic teachings and educating Muslim communities personally who do not yet have a strong understanding of the religion, especially in interpreting evidence from the Qur'an and Sunnah. This is very important because misinterpretation is the precursor to extremist actions by radicals.